Comparison of the Opinions of Modern Exegists and Theologians Regarding Good and evil - Syeda Ayesha Rizvi; Dr. Sabeen Akbar (jihat-ul-islam, 2023)
Like the traditional exegists, many modern exegists have also incorporated the discussions of good and evil into their exegesis. Among them we chose three commentators: Mawlānā Abu al-Kalām Āzād, Amīn Aḥsan Iṣlāḥī and Abdul Ḥaq Ḥaqqānī. The discussions related to good and bad will be explained in this chapter with the interpretations of these three exegists. These three exegists are widely accepted among scholars, they have presented valuable scholarly studies on their topics. Based on the acceptance of these exegesis among the scholars and their valuable discussions, we will present the discussions of good and bad among them which are as follows.